Integrating Halal-Thayyib Food Values into Islamic Education: A Systematic Review from the Perspectives of Food Ethics, Arabic Education, and Educational Management - Saputra, Reza; Jariyah, Ainun; Lestari, Ana Dwi; Rahman, Habibur; Hamidah, Husnul; Razida, Mirdawati; Elyas, Yusril Ihza; Ubaidillah, Moch (Journal of Posthumanism, 2025)
This study aims to systematically examine the integration of halal-thayyib values in Islamic education through the perspectives of food ethics, Arabic linguistics, and education management. Using a Systematic Literature Review (SLR) approach based on PRISMA guidelines, this study analyzes 30 selected articles from Scopus and Google Scholar databases published in 2015-2025 that have been evaluated through the JBI Critical Appraisal Checklist. the Qur’anic theological foundations and semantics of the term halal-thayyib in Arabic linguistic studies; ecopedagogical approaches and environmental awareness; social justice in the food supply chain; nutritional literacy and food safety; and managerial and pedagogical strategies in implementing values in Islamic educational institutions. The findings suggest that an interdisciplinary approach combining food ethics, Arabic language and education management has the potential to strengthen ethical food agency and shape a contextualized and transformative Islamic curriculum. This article offers a conceptual framework and strategic recommendations for educators, education managers, and policy makers in integrating halal-thayyib values holistically in contemporary Islamic education.